Analisis Keuangan Agroindustri Keripik Singkong "Kita Suka Dua Putra" di Kecamatan Malalayang - Ulfa Hastuti Sugiarto (COCOS, 2012)
Ulfa Hastuti Sugiarto. Financial Analysis Agroindusri Cassava Chips "We Love Two Son" In the district under the guidance of JR Mandei Malalayang, as chairman of the Th. M. Katiandagho, and L. R. J. Pangemanan as a member. This study aims to determine the financial condition viewed from the level of liquidity, solvency, and profitability based on data from financial statements. The data used are the primary data from industries cassava chips We Like Son Two. In District Malalayang. Data was collected through direct interviews with business owners cassava chips. Data analysis methods used are the deskritif analysis presented in the form of financial statement balance sheet and income statement and then analyzed by looking at comparisons of financial ratios. Based on survey results revealed the sales results in 2010 were Rp.666.000.000 and in 2011 was Rp.863.928.000 with average sales per day is for a total of 36 kg kilogram size, pack size of 30 packs, and as many as 2000 retail size packs. In the profit / loss is known in the year 2010 net income was Rp.186.140.600 and in 2011 for Rp.180.024.200. These results showed a decrease of Rp.19.121.800 this is due to increased operating expenses. And profit after interest and taxes (EAIT) in 2010 was Rp.186.140.600 and in 2011 for Rp.172.824.200. These results showed a decrease of Rp.13.316.400 this is due to increased operating expenses and interest expenses. Known in the balance sheet total assets and passive in the year 2010 amounted to Rp.97.061.000 with the passive for the debts do not exist and the capital of Rp.97.061.000. In 2011, total assets and passive is Rp. 118 337 800 to the passive side of Rp.26.933.600 debt and capital of Rp.91.404.200. Of the profit / loss and balance sheet can be measured ratio, financial ratio. Liquidity ratio measurement results for the year 2010 can not be calculated because this year has no debt While the year 2011 for the current ratio and quick ratio 13.18 11.89 This shows the condition where the condition of the company are better than other businesses based on industry standards. The results of measurements of the solvency ratio in 2010 can not be calculated because this year the company has not owned the debt while in 2011memperoleh results showed 23% of the amount of debt funding slightly, making it easier for companies to apply for additional loans. Profitability ratio measuring results in 2010 for the gross profit margin of 42%, net profit margin of 28%, an ROI of 192%, and ROE of 192% results show the state that the company is in good condition be caused measurement result is above the industry standard. In the year 2011 to the gross profit margin, net profit margin, ROI, and ROE was 35% sequentially, 20%, 142% and 189% results demonstrate good corporate state in which the measurement is above the industry standard.